A Three-Dimensional Model of Women’s Empowerment: Implications in the Field of Microfinance and Future Directions - Huis, Marloes A.; Hansen, Nina; Otten, Sabine; Lensink, Robert (Frontiers in Psychology, 2017)
Women’s empowerment is an important goal in achieving sustainable development worldwide. Offering access to microfinance services to women is one way to increase women’s empowerment. However, empirical evidence provides mixed results with respect to its effectiveness. We reviewed previous research on the impact of microfinance services on different aspects of women’s empowerment. We propose a Three-Dimensional Model of Women’s Empowerment to integrate previous findings and to gain a deeper understanding of women’s empowerment in the field of microfinance services. This model proposes that women’s empowerment can take place on three distinct dimensions: (1) the micro-level, referring to individuals’ personal beliefs as well as actions, where personal empowerment can be observed (2) the meso-level, referring to beliefs as well as actions in relation to relevant others, where relational empowerment can be observed and (3) the macro-level, referring to outcomes in the broader, societal context where societal empowerment can be observed. Importantly, we propose that time and culture are important factors that influence women’s empowerment. We suggest that the time lag between an intervention and its evaluation may influence when empowerment effects on the different dimensions occur and that the type of intervention influences the sequence in which the three dimensions can be observed. We suggest that cultures may differ with respect to which components of empowerment are considered indicators of empowerment and how women’s position in society may influence the development of women’s empowerment. We propose that a Three-Dimensional Model of Women’s Empowerment should guide future programs in designing, implementing, and evaluating their interventions. As such our analysis offers two main practical implications. First, based on the model we suggest that future research should differentiate between the three dimensions of women’s empowerment to increase our understanding of women’s empowerment and to facilitate comparisons of results across studies and cultures. Second, we suggest that program designers should specify how an intervention should stimulate which dimension(s) of women’s empowerment. We hope that this model inspires longitudinal and cross-cultural research to examine the development of women’s empowerment on the personal, relational, and societal dimension.